PENGGUNAAN MEDIA CUBARITME UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PENJUMLAHAN PADA MURID TUNANETRA KELAS DASAR III DI UPT SLB NEGERI 1 SINJAI - ana indrayana; Zulfitrah Zulfitrah; Syamsuddin Syamsuddin (-, 2024)
This research is based on the problem of the low numeracy skills of blind students in elementary class III at UPT SLB Negeri 1 Sinjai. The aim of this research is to determine the increase in the ability to calculate addition through the use of cubarithm media in blind students in elementary class III. This research uses a quantitative approach with descriptive research presented in the form of a bar chart. The subject of this research was 1 class III blind student. Data collection in this research used written tests in the form of essay questions. The results of the study showed an increase in the ability to calculate addition in blind students in elementary class III at UPT SLB Negeri 1 Sinjai after using cubarithm media. The conclusions of this research are (1) the ability to calculate addition in elementary class III blind students before being given treatment using cubarithm media was in the poor category. (2) the ability to calculate addition in elementary class III blind students after being given treatment using cubarithm media is in the very good category. (3) there is an increase in the ability to calculate addition through the use of cubarithm media in blind students in elementary class III at UPT SLB Negeri 1 Sinjai.